The isotopic composition of dissolved cadmium in the water column of the West Philippine Sea - Yang, Shun-Chung; Lee, Der-Chuen; Ho, Tung-Yuan; Wen, Liang-Saw; Yang, Hsu-Han (Frontiers in Marine Science, 2014)
The dissolved concentration and isotopic compositions of cadmium (Cd) in the seawater of the West Philippine Sea were determined. In general, Cd isotopic composition in the water column decreased with depth, with ε114/110Cd (ε114/110Cd = [(114Cd/110Cd)sample / (114Cd/110Cd)NIST 3108 - 1]×10000) ranging from +7.2 to +10.1 in the top 60 m, from +4.8 to +5.1 between 100 and 150 m, peaking at +8.2 at 200 m, decreasing from +4.5 to +3.3 from 400 to 1000 m, and remaining constant at +3.0 from 1000 m and deeper. Different to a Rayleigh fractionation model, the isotopic composition and log scale concentrations of Cd do not exhibit a linear relationship. However, from the deep water to thermocline, the variations in Cd concentration and ε114/110Cd are relevant to the variations of temperature and salinity, indicating that water mixing is the dominant processes determining the concentration and isotopic composition in the interval. At 200 m where North Pacific Tropic Water dominates the water mass, the elevated ε114/110Cd could be linked to the composition in the upper portions of the water mass. In the top 150 m, the ε114/110Cd varies similarly to the phytoplankton community structures, implying that Cd uptake by various phytoplankton species may be associated with the isotopic variation. However, the effects of atmospheric inputs to the ε114/110Cd in the surface water cannot be excluded. A box model calculation is used to constrain the contributions of various processes to the Cd isotopes of surface water, and the results indicate that the Cd concentration and isotopic composition in most of the water body of the region are controlled by physical mixing, while the effects of biological fractionation and atmospheric inputs are limited in the euphotic zone.